"Mild" Uncoupling of Mitochondria. Issue 3 (June 1997) - Starkov, A. A.
Abstract : Recently, it was proposed that the thyroid hormone-mediated uncoupling in mitochondria is involved in the cellular defence system against free radicals (Skulachev V.P. (1996) Quart. Rev. Biophys. 29: 169–202). This phenomenon was named "mild" uncoupling. It was postulated to be a protein-mediated process controlled by several factors. The data reported during the past 40 years, pointing to the protein-mediated uncoupling mechanism in mitochondria, are reviewed in a context of hypothetical properties of "mild" uncoupling. The mechanism of "mild" uncoupling is suggested to be the following: (a) mitochondria possess protein(s) that regulate the proton permeability of inner mitochondrial membrane; (b) these proteins are regulated by binding of an unidentified low-molecular-weight endogenous compound with properties resembling those of the most active artificial uncouplers like FCCP and SF6847; (c) the interaction of this compound with its target protein(s) is modulated by a thyroid hormone in a positive (i.e. enhancing the proton permeability) way and by sex steroid hormones in a negative way; (e) endogenous fatty acids can attenuate the influence of both thyroid and steroid hormones.